The contribution of the nurse manager to healthy labour relations: Part 2 - Marthie Bezuidenhout (AOSIS, 1998)
This study had its origins in the continuing evidence that health services in South Africa were increasingly being implicated in labour unrest. Opsomming Die studie het sy oorsprong in voortgesette bewyse dat die gesondheidsdienste in Suid-Afrika tot 'n al groter mate betrek word in arbeidsonrus. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.